Pengaruh Indeks Saham Regional dan Indeks Internasional Terhadap Jakarta Stock Exchange Composite (JKSE) Periode Juni 2024 - Mei 2025 - Siti Mahmudah Qodariyah; Sugeng Priyanto (LPPM Politeknik Pratama, 2026)
This study investigates the influence of regional and international stock indices on the Jakarta Stock Exchange Composite (JKSE) during the period from June 2024 to May 2025. The regional indices examined are the Kuala Lumpur Stock Exchange (KLSE, Malaysia), Straits Times Index (STI, Singapore), and Shanghai Stock Exchange Composite (SSEC, China). The international indices include the Dow Jones Industrial Average (DJIA, United States) and Nikkei 225 (N225, Japan). A total of six stock indices were selected using purposive sampling based on their relevance to the Indonesian market, resulting in 198 daily closing price observations sourced from the official investing.com website. The findings indicate that the KLSE and STI significantly affect the JKSE, whereas the SSEC, DJIA, and Nikkei 225 (N225) do not exhibit a significant impact on the JKSE